Community and Family-Focused Public Health and Sustainable Development - Zukiewicz-Sobczak, Wioletta; Wojtyla-Buciora, Paulina; Rącka, Izabela; Wojtyla, Andrzej (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The book "Community and Family-Focused Public Health and Sustainable Development" was originally published in the renowned International Journal of Environmental Research and Public Health. This Special Issue encompassed novel aspects of applications that are connected with sustainability issues in community and family-focused public health studies. Contributions have a significant impact on solving public health problems at the family and community levels. The Special Issue originally published scientific papers, including review articles, that fell under this Special Issue's remit and that were relevant to audiences worldwide. Currently, the term "family health" is most commonly to describe mother and child health and reproductive health. It is rare for family health to include the family as an important context for health development and that includes all family members and the family's social environment. Authors of scientific research covering issues related to the impact of the family and the environment in which the family lives and functions on its members' health in the present and in the future were encouraged to contribute their work. In addition, we were especially interested in scientific reports on social, economic, and health inequalities in the context of achieving the sustainable development goals.